The Phenomenon That Influenced The Development of Cool Japan in Indonesia - Fitri Alfarisy; Aditya Prayoga; Ayu Alfi Syahrina; Nadya Salma Salsabila (Journal Of Social Research, 2021)
As it is well known that Japan has many unique cultures that can attract people from other countries. Since the mid-1960s, Japanese culture, especially popular culture, has continued to develop to this day. The peak of its development was in 2002, when an article written by Douglas McGray entitled " Japan's Gross National Cool " was published in Foreign Policy Magazine. This article is the reason for the emergence of a new term called Cool Japan , which is used to describe all cultures originating in Japan. Japan then used Cool Japan as one of its diplomatic strategies, especially for countries in Southeast Asia. As a cultural diplomacy strategy, Cool Japan has several advantages or benefits for the Japanese Government, such as: to build a positive image to the people of Southeast Asia, to develop the country's economy through the cultural industry as well as a tool to compete with cultural products from China and South Korea.